DESIGN OF INCENTIVE WAGES WITH STANDARD TIME TO IMPROVE PACKAGE OPERATOR PERFORMANCE (A Case Study at PT. XYZ) - Nana Rahdiana; Sani Suhardiman; Khoirudin Khoirudin (Universitas Ahmad Dahlan Indonesia, 2021)
XYZ is a company engaged in the paper industry, which is located in West Java. Since established in 1976, this company has produced photocopy paper in the form of reams. This company has advantages in terms of paper quality so that its products dominate the international market and the domestic market. With a very tight level of market competition, companies must continue to work optimally to continuously improve employee performance and company productivity. The purpose of this study is to plan an incentive-based employee wage system, which is suitable and in accordance with company conditions. Incentive wages are important as one of the main components to increase and maintain motivation, performance and work integrity. This research was conducted in the Finishing Department of the copy manual wrapping work unit. The method used are the Piecework method, the Halsey method, and the Rowan method. The result of this research is a comparison of the amount of wages between the wage system used by the company and the three methods of incentive pay as a company alternative. From the comparison of the three incentive wage design methods, the authors recommend the Halsey method as the best method that is able to provide benefits for both the company and for workers which we call dual mutualism. The Halsey method still guarantees a basic wage and a decent incentive wage for workers as a motivation to work faster and better.